2009
DOI: 10.1002/tox.20508
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides and polychlorinated biphenyls in fin whales (Balaenoptera physalus) from the Gulf of California

Abstract: The present study reports unique data on concentrations of several classes of organochlorine pesticides and polychlorinated biphenyls in blubber biopsies from healthy living fin whales (Balaenoptera physalus) from the Gulf of California, Mexico, one of the most isolated and unstudied population in the world. OC levels in this population were generally lower than levels reported in fin whales from other regions. The rank order of OCs were SigmaDDTs (range from 300 to 2400 ng g(-1) lw) > SigmaPCBs (range from 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Nino- Torres et al ( 2010 ) reported in DDT levels in blubber biopsies from fi n whales ( Balaenoptera physalus ) collected in [2004][2005] in the Gulf of California, Mexico. DDT levels ranged from 200 to 1,900 ppb with an average of 500 ppb in females and 850 ppb in males.…”
Section: Ddt In Marine Mammalsmentioning
confidence: 99%
“…Nino- Torres et al ( 2010 ) reported in DDT levels in blubber biopsies from fi n whales ( Balaenoptera physalus ) collected in [2004][2005] in the Gulf of California, Mexico. DDT levels ranged from 200 to 1,900 ppb with an average of 500 ppb in females and 850 ppb in males.…”
Section: Ddt In Marine Mammalsmentioning
confidence: 99%
“…A large variety of synthetic organic chemicals such as organochlorine pesticides (OCPs) have been released into the environment over the last few decades (Valeron et al,2009). As widespread environmental pollutants, OCPs are highly lipophilic and chemically stable compounds that persist in the environment and accumulate in the food chain and in human tissues (Alvarez‐Pedrerol et al,2008; Niño‐Torres et al,2010). 2,2‐Bis (4‐chlorophenyl)‐1,1,1‐trichloroethane (DDT), the first widely used synthetic organochlorine pesticide, was given credit for having helped one billion people live free from malaria.…”
Section: Introductionmentioning
confidence: 99%
“…While the western coast of the Gulf remains comparatively undisturbed, many eastern coastal areas and catchments draining into the Gulf are affected by aquaculture, industry, agriculture, and urban development (Beman et al ., ; Páez‐Osuna and Ruiz‐Fernández, ; Lluch‐Cota et al ., ). Intensive use of pesticides in agricultural areas is also a concern (Gutierrez‐Galindo et al ., ; Galindo‐Reyes et al ., ; Niño‐Torres et al ., ). Alteration of freshwater and sediment inputs from the Colorado River has modified the habitat for commercial and endangered species (Carriquiry and Sánchez, ; All, ; Rowell et al ., ).…”
Section: Methodsmentioning
confidence: 99%